2022
DOI: 10.1038/s41398-022-01962-6
|View full text |Cite
|
Sign up to set email alerts
|

Associations of plasma angiostatin and amyloid-β and tau levels in Alzheimer’s disease

Abstract: Angiostatin, an endogenous angiogenesis inhibitor generated by the proteolytic cleavage of plasminogen, was recently reported to contribute to the development of Alzheimer’s disease (AD). However, whether there are pathological changes in angiostatin levels in individuals with AD dementia is unclear, and whether plasma angiostatin has a relationship with major AD pathological processes and cognitive impairment remains unknown. To examine plasma angiostatin levels in patients with AD dementia and investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…In accordance with our previous study, the plasma levels of pT217, pT181, and NfL were simultaneously measured using the commercially available single-molecule array (SIMOA) Human Neurology 3-Plex A assay kit (Quanterix, USA) on board of the automated SIMOA HD-1 analyzer (Quanterix). 24 Plasma levels of CTRP3 (SEK169Hu, Cloud-Clone Corp., Hubei, China), CTRP4 (MM-1640H1, Jiangsu Meimian Industrial Co., Ltd., Jiangsu, China), and CTRP14 (SEE867Hu, Cloud-Clone Corp.) were detected using commercially available ELISA kits according to the instructions.…”
Section: Biochemical and Molecular Investigationsmentioning
confidence: 99%
“…In accordance with our previous study, the plasma levels of pT217, pT181, and NfL were simultaneously measured using the commercially available single-molecule array (SIMOA) Human Neurology 3-Plex A assay kit (Quanterix, USA) on board of the automated SIMOA HD-1 analyzer (Quanterix). 24 Plasma levels of CTRP3 (SEK169Hu, Cloud-Clone Corp., Hubei, China), CTRP4 (MM-1640H1, Jiangsu Meimian Industrial Co., Ltd., Jiangsu, China), and CTRP14 (SEE867Hu, Cloud-Clone Corp.) were detected using commercially available ELISA kits according to the instructions.…”
Section: Biochemical and Molecular Investigationsmentioning
confidence: 99%
“…Since the generation of neuritic plaques composed of amyloid-β (Aβ) peptides is a major pathological hallmark of AD, Aβ is a key predictor for the early diagnosis of AD. 4–6 Amyloid beta 1-40 (Aβ 1-40) is one of the most abundant substances in the body with the capacity to form insoluble aggregates, which is a universal biomarker used for the prediction of AD. 7–9 Recent studies have demonstrated that the overexpression of Aβ 1-40 in serum predicts AD and exhibits a strong correlation with pathological changes in the brain.…”
Section: Introductionmentioning
confidence: 99%